SIK2: A Novel Negative Feedback Regulator of FGF2 Signaling - Kuser‐Abali, Gamze; Ugurlu‐Bayarslan, Asli; Yilmaz, Yeliz; Ozcan, Ferruh; Karaer, Funda; Bugra, Kuyas (Wiley, 2024)
AbstractA wide range of cells respond to fibroblast growth factor 2 (FGF2) by proliferation via activation of the Ras/ERK1/2 pathway. In this study, the potential involvement of salt inducible kinase SIK2) in this cascade within retinal Müller glia is explored. It is found that SIK2 phosphorylation status and activity are modulated in an FGF2‐dependent manner, possibly via ERK1/2. With SIK2 downregulation, enhanced ERK1/2 activation with delayed attenuation and increased cell proliferation is observed, while SIK2 overexpression hampers FGF2‐dependent ERK1/2 activation. In vitro kinase and site‐directed mutagenesis studies indicate that SIK2 targets the pathway element GRB2‐associated‐binding protein 1 (Gab1) on Ser266. This phosphorylation event weakens Gab1 interactions with its partners growth factor receptor‐bound protein 2 (Grb2) and Src homology region 2 domain containing phosphatase 2 (Shp2). Collectively, these results suggest that during FGF2‐dependent proliferation process ERK1/2‐mediated activation of SIK2 targets Gab1, resulting in downregulation of the Ras/ERK1/2 cascade in a feedback loop.
Keywords: Feedback, Physiological; Mice; MAP Kinase Signaling System; Animals; Humans; Fibroblast Growth Factor 2; Protein Serine-Threonine Kinases; Phosphorylation; Adaptor Proteins, Signal Transducing; Cell Proliferation; Signal Transduction; GRB2 Adaptor Protein